Thoracic combined spinal epidural anaesthesia for exploratory laparoscopy and laparotomy (sigmoidectomy, colostomy): The first case in Palestine for the ASA5 patient - Samah A Maree; Anoud Jadou; Mahmoud R Manasra; Khaled Temezeh; Falah Ibedo (SAGE Open Medical Case Reports)
Thoracic combined spinal epidural anaesthesia offers the ideal perioperative anaesthesia and analgesia. A 78-year-old female presented to our hospital with a hypertensive emergency, non-ST elevation myocardial infarction and pulmonary effusion. Then the patient had abdominal pain, constipation and vomiting. When examined, there was significant abdominal distention. During a colonoscopy, there was a fungating mass lesion 20 cm from the anal verge. A biopsy was taken and showed intramucosal adenoma within tubulovillous adenoma with high-grade dysplasia. The patient underwent exploratory laparoscopy and laparotomy (sigmoidectomy, colostomy) under thoracic combined spinal epidural anaesthesia at T9–T10 interspinous space. The patient was classified as ASA5 according to the American Society of Anesthesiologists physical status. The guidelines recommend utilizing regional anaesthesia instead of general anaesthesia for compromised elderly patients. In our case, we report the first case in Palestine of an ASA5 patient who successfully underwent abdominal surgery under thoracic combined spinal epidural anaesthesia.